Problems in bariatric patient care – challenges for dieticians - Kostecka, Małgorzata (Wideochir Inne Tech Maloinwazyjne, 2017)
Obesity management options include a low-calorie diet, behavioral therapy, regular physical activity and pharmacological therapy. However, treatment failure is frequently encountered, most of these methods are ineffective, and a positive outcome is rarely maintained in the long term. In morbidly obese patients, bariatric surgery is considered the most effective treatment for obesity as well as the accompanying diseases. Bariatric surgery promotes much greater weight loss than conservative treatment, regardless of the applied surgical technique. Bariatric surgery patients should receive professional perioperative (preoperative, intraoperative and postoperative) care from a multidisciplinary team of specialists, including a bariatric surgeon, a general practitioner, a dietitian and a health psychologist. Patients require postoperative nutritional counseling to be able to stabilize their weight and maintain long-term weight loss after surgery. Patients are guided by bariatric dietitians through the process of adopting new eating habits and behavior, learning how to make healthy food choices.